The Atlastin C-terminal Tail Is an Amphipathic Helix That Perturbs the Bilayer Structure during Endoplasmic Reticulum Homotypic Fusion - Faust, Joseph E. (J Biol Chem, 2015)
Fusion of tubular membranes is required to form three-way junctions found in reticular subdomains of the endoplasmic reticulum. The large GTPase Atlastin has recently been shown to drive endoplasmic reticulum membrane fusion and three-way junction formation. The mechanism of Atlastin-mediated membrane fusion is distinct from SNARE-mediated membrane fusion, and many details remain unclear. In particular, the role of the amphipathic C-terminal tail of Atlastin is still unknown. We found that a peptide corresponding to the Atlastin C-terminal tail binds to membranes as a parallel α helix, induces bilayer thinning, and increases acyl chain disorder. The function of the C-terminal tail is conserved in human Atlastin. Mutations in the C-terminal tail decrease fusion activity in vitro, but not GTPase activity, and impair Atlastin function in vivo. In the context of unstable lipid bilayers, the requirement for the C-terminal tail is abrogated. These data suggest that the C-terminal tail of Atlastin locally destabilizes bilayers to facilitate membrane fusion.